Evaluation of the implementation of the village fund allocation policy - Istifazhuddin, Alif Hazmi; Mardiyanta, Antun (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The village fund allocation policy was introduced in Indonesia to enhance village financial capacity and autonomy. However, despite the implementation of Law No. 6/2014 on Villages, many villages, including Nguwok Village, still experience constraints in fully utilizing the village fund allocation funds due to regulatory control from the local government. This research aims to evaluate the implementation process of the village fund allocation in Nguwok Village, focusing on the allocation, utilization, and effectiveness of the funds within the framework of fiscal decentralization and village autonomy. Methods: This study employs a qualitative descriptive approach with purposive sampling to select key informants. Data collection methods include observations, document analysis, and in-depth interviews with stakeholders such as the Lamongan Regency Government, Modo Subdistrict Office, and Nguwok Village Administration. Findings: Out of seven effectiveness criteria, only three (range, frequency, and bias) were met, while access, service precision, program compatibility, and accountability remain ineffective. The village fund allocation implementation process is also found to be inefficient, with budgeting reports lacking transparency and not detailing fund expenditures. Conclusions: While the village fund allocation funds significantly contribute to Nguwok Village’s financial capacity, village autonomy remains constrained by local government regulations. Despite smooth intergovernmental coordination and timely fund disbursement, village-level decision-making power is limited, and public participation is insufficient. Additionally, budget transparency issues persist, with incomplete reporting of fund utilization. To fully realize village autonomy, the Nguwok Village government must take a more proactive role in decision-making rather than merely following district-level guidelines. Novelty/Originality of this Article: This study provides a critical evaluation of the limitations of the village fund allocation policy implementation despite the legal framework supporting fiscal decentralization. By highlighting the gap between policy and practice, this research offers practical recommendations for improving village autonomy, community participation, and financial transparency.